The Impact of Tax Data Clarification Requests, Tax Literacy, and Moral Obligation on Tax Compliance - Imam Syafii; Lilis Ardini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the influence of the Request for Explanation of Data and/or Information (SP2DK), tax understanding, and tax morale on individual taxpayer compliance in the KPP Pratama Pamekasan and Bangkalan areas. This research is motivated by the persistent fluctuations in taxpayer compliance within Indonesia’s self-assessment system, seeking to test whether internal motivational factors play a more significant role than administrative enforcement mechanisms. This study employs a quantitative approach using a survey method by distributing questionnaires to 92 respondents selected through purposive sampling. Data analysis was performed using multiple linear regression, preceded by validity, reliability, and classical assumption tests to ensure the robustness of the model. The results indicate that SP2DK does not have a significant influence on taxpayer compliance. In contrast, tax understanding and tax morale positively and significantly influence compliance behavior, with tax morale emerging as the most dominant predictor. These findings suggest that internal psychological drivers are more decisive than administrative supervision in improving voluntary tax compliance. This study provides an original contribution by demonstrating that, within the context of the Madura region, tax compliance is driven more by intrinsic motivation and educational awareness than by administrative enforcement. It emphasizes the importance of shifting tax policy toward behavioral and educational approaches to foster long-term voluntary compliance.